2009
DOI: 10.1519/jsc.0b013e3181aa1d9f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physical Characteristics and Performance Among Elite Snowboarders

Abstract: There are little scientific data regarding snowboarding and the physiological demands on snowboarders. The aim of this study was to assemble and evaluate a battery of tests for the snowboard disciplines parallel, snowboard cross (SBX), big air, and half-pipe (HP). Thirty-seven competitive snowboarders participated in the study and completed a test battery that comprised tests for aerobic capacity, balance, jumping, isokinetic core power, isokinetic leg power, isometric bench press, isometric bench pull, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 11 publications
6
48
1
1
Order By: Relevance
“…For instance, for rock climbing Magiera et al (2013) found that the physiological and anthropometric characteristics explained 38% of the climber's performance capacity. For elite snowboarders, the predictive value of the results on a test battery comprising physical tests (e.g., aerobic capacity, balance, isokinetic power) was even higher as it explained more than 60% of the variance of snowboard performance (Platzer, Raschner, Patterson, & Lembert, 2009). …”
Section: The Physical Competencesmentioning
confidence: 99%
“…For instance, for rock climbing Magiera et al (2013) found that the physiological and anthropometric characteristics explained 38% of the climber's performance capacity. For elite snowboarders, the predictive value of the results on a test battery comprising physical tests (e.g., aerobic capacity, balance, isokinetic power) was even higher as it explained more than 60% of the variance of snowboard performance (Platzer, Raschner, Patterson, & Lembert, 2009). …”
Section: The Physical Competencesmentioning
confidence: 99%
“…However, there are disciplines in which the level of technical skill does not differentiate athletes in terms of body stability. These disciplines include surfing, judo, alpine skiing, and, indeed, snowboarding [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are sports in which the level of technical advancement does not determine the body's level of stability. These include surfing, judo, snowboarding and alpine skiing [11,21].…”
Section: Discussionmentioning
confidence: 99%